Effects of T6 treatment on the microstructural changes, hardness and thermal analysis of As-Cast Al-Si-Mg alloys - Izrul Azree Mohd Zaki (Universiti Malaysia Perlis, 2009)
Aluminium-silicon-magnesium is usually applied in automotive industry such as in block engine. The main objective of this project is to study the changes in microstructure, hardness and the thermal analysis curve after the sample were processed starting from as received, as-cast, solution treatment at 5100C for four hours and quenched in the iced water. The process was followed by four hours of aging treatment and nine hours of aging treatment at 1800C at two different samples. After casting, each of the samples was also cut to three different portions which are top, middle and bottom to see the microstructure changes and hardness. At the end of the study, the hardness result shows an increasing value after going through each of the process but the hardness for four hours aging is higher compare to nine hours aging. The result is expected between top, middle and bottom are also different from each other.